2020
DOI: 10.18186/thermal.672785
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characterization of Multi-Phase Particulate Slurry in Thermal Power Plants Using Computational Fluid Dynamics

Abstract: The key issue associated with the thermal power plant is the disposal of ash-water slurry and the process of its transportation is accomplished using long length pipelines. The designing of such pipelines is a vital endeavor of researchers and designers globally. In this perspective, numerical simulation of 42 mm diameter three-dimensional slurry flow pipeline carrying high concentration of mono-dispersed fine ash particles has been carried out. The study is enunciated by employing Eulerian-Eulerian two-phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Other areas in using CFD for numerical study of fluid flow and particle trajectory includes one bed hospital, particle motion in ICU, air pollution in hospital modelling, ventilation of hospital rooms, deposition of particle and air flow in IC Engines, nano-fluid study, fluid flow and pressure distribution in bearings etc. [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. While CFD is an effective tool for numerical study, other numerical study involving ANN may be conducted for enhancing the results, as studies reported earlier have confirmed the same [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 92%
“…Other areas in using CFD for numerical study of fluid flow and particle trajectory includes one bed hospital, particle motion in ICU, air pollution in hospital modelling, ventilation of hospital rooms, deposition of particle and air flow in IC Engines, nano-fluid study, fluid flow and pressure distribution in bearings etc. [31][32][33][34][35][36][37][38][39][40][41][42][43][44]. While CFD is an effective tool for numerical study, other numerical study involving ANN may be conducted for enhancing the results, as studies reported earlier have confirmed the same [45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 92%
“…Hence, the pipe geometry containing 462 k elements is finalized to carry out the simulation in order to save the computational time. The present geometric model of straight pipe was adopted form Parkash et al [39]. Additionally, the orthogonal quality of the chosen mesh geometry is 0.934, which is very high in the present case.…”
Section: Mesh Independency Testmentioning
confidence: 99%
“…Many numerical simulations of gas-liquid two-phase flow have used the Eulerian model in different geometries including sudden expansion [23] and flow in a horizontal tube [24] because it has proven to be more accurate than the VOF and Mixture models [23]. In the Eulerian approach, the liquid phase and vapour phase are both treated as separate continuous phases determined by the volume fraction for each phase [25,32]. The Eulerian two-phase model solves a set of two-phase differential equations for each phase, so it is the most complex of the two-phase models [23].…”
Section: Cfd Two-phase Flow Modellingmentioning
confidence: 99%